APLIKASI FORMULA BOKASHI KOTORAN SAPI DAN TKKS DARI SISKA BENGKULU PADA TANAMAN KELAPA SAWIT ( Elaeis guinnensis Jack) MENGHASILKAN (TM) - Nurseha Nurseha; Sunarti Sunarti; Sri Mulatsih (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2016)
The aim of this research was to now effects of bokashi formulation made of cow manure and empty oil palm fruit bunches from SISKA Bengkulu on immature oil palm plants which had been done on January to Oktober 2016 in Babatan village, Sukaraja sub-distric, Seluma distric, Bengkulu Province.This is the second year of two years research planning funded by Hibah Bersaing with the title of Formulation of Bokashi of Cow manure and empty oil palm fruit bunches from SISKA Bengkulu on Sustainable Oil Palm.This research used Randomized Complate Block Design (RCBD) to evaluate 6 treatment were F0 = control; F1 = cow manure; F2 = 1/3 of cow manure + 2/3 of empty fruit bunch; F3 = = 1/2 of cow manure + 1/2 of empty fruit bunch; F4 == 2/3 of cow manure + 1/3 of empty fruit bunch; and F5 = empty fruit bunch.The study concluded that 1.The treatment of bokashi of cow manure and empty oil palm fruit bunches from SISKA Bengkulu had very significant affects on the production of fresh fruit bunches at 4 -8 months after fertilizer application, where F0 treatment (control) to produce fresh fruit bunches high of 72.17 kg per plant, significantly different from the treatment of F1 = 11.5 kg per plant, F2 = 38.33 kg per plant, F3 = 27.83 kg per plant, F4 = 22.83 kg per plant, and F5 = 27.33 kg per plant. 2. The treatment of bokashi of cow manure and empty oil palm fruit bunches from SISKA Bengkulu had very significant affects on the production of fresh fruit bunches at 4 -8 months after fertilizer application where F0 treatment (control) produced 72.17 kg of fresh fruit bunches per plant, no significant different from the treatment of F1 = 70.17 kg per plant, F2 = 82.83 kg per plant, F3 = 72.0 kg per plant, and F4 = 87.92 kg per plant, illustrating that bokashi fertilizer waste SISKA with various formulas can replace the use of chemical fertilizers, even significantly treatment F5 able to produce fresh fruit bunches higher than the F0 which could reach 128.17 kg per plant.Keywords : Bokashi, fresh fruit bunches , cow manure,Siska Bengkulu